2020
DOI: 10.12998/wjcc.v8.i24.6373
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary malignant melanoma diagnosed with percutaneous biopsy tissue: A case report

Abstract: BACKGROUND Primary malignant melanoma of the lung (PMML) is a rare and highly malignant tumor with a poor prognosis. Here, we report a PMML case diagnosed by computed tomography (CT)-guided percutaneous biopsy, describe its pathological features and review relevant literature to improve our understanding of this tumor. CASE SUMMARY A 64-year-old Chinese female presented with productive cough for 7 mo. A chest CT scan showed a large and space-occupying lesion in Lingual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Summarizing the literature (1,3,4,7,(11)(12)(13)(14)(15) on lung melanin in recent years, we found that: (I) Pulmonary melanoma has no specific clinical manifestations, but it is frequently characterized by coughing, hemoptysis, dull chest pain, and other symptoms. (II) It is more likely to occur in the lower lobe of the left lung, the metastasis rate of mediastinal lymph nodes is lower than that of lung cancer, and the mutation rate of BRAF is low, but the prognosis is poor, and the median survival is 24.3 months.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Summarizing the literature (1,3,4,7,(11)(12)(13)(14)(15) on lung melanin in recent years, we found that: (I) Pulmonary melanoma has no specific clinical manifestations, but it is frequently characterized by coughing, hemoptysis, dull chest pain, and other symptoms. (II) It is more likely to occur in the lower lobe of the left lung, the metastasis rate of mediastinal lymph nodes is lower than that of lung cancer, and the mutation rate of BRAF is low, but the prognosis is poor, and the median survival is 24.3 months.…”
mentioning
confidence: 88%
“…Melanoma, a highly malignant and aggressive tumor, is most commonly found in the skin but can also occur in the respiratory tract and oral cavity. Primary pulmonary melanoma is extremely rare, accounting for only 0.01% of all primary lung tumors (1). The prognosis is extremely poor, with most patients living for less than 18 months (2).…”
Section: Introductionmentioning
confidence: 99%